A Study on the Influence of Effective Teamwork on Employee Performance in Civil Industries (International Journal of Food and Nutritional Sciences, 2022)
Individuals in today's societies have been emphasizing for reaching occupational objectives and goals at work more than the notion of collaboration. Furthermore, the value of cooperation as a crucial tool in the workplace seems to be ignored by both employers and workers, resulting in low productivity and performance in their employment. The study focused primarily on elements connected with the collaborative approach in the workplace and their impact on employee performance within the civil industries. The objectives of this study were to identify collaboration-related elements, determine the positive and negative impacts of teamwork on workers, and investigate the influence of teamwork on organizational performance. However, there has been very little objective investigation on whether cooperation has any influence on productivity in the service industry so far. This investigates the intangible character of services and also the resulting difficulty in evaluating production. Future studies may incorporate a wider sample by studying additional organizations, such as industrial enterprises, financial firms and many more to compare findings. Future studies may compare socio-demographic variations and motivating variables across industries.